2014
DOI: 10.1161/circresaha.114.303180
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Mesenchymal Stem Cells Produce Concordant Improvements in Regional Function, Tissue Perfusion, and Fibrotic Burden When Administered to Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Rationale While accumulating data support the efficacy of intramyocardial cell-based therapy to improve LV function in patients with chronic ischemic cardiomyopathy undergoing CABG, the underlying mechanism and impact of cell injection site remain controversial.Mesenchymal stem cells (MSCs) improve LV structure and function through several effects including: reducing fibrosis, neoangiogenesis and neomyogenesis. Objective To test the hypothesis that the impact on cardiac structure and function following intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
235
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(252 citation statements)
references
References 50 publications
4
235
0
5
Order By: Relevance
“…Research from several laboratories, including ours, suggests that stem cells hold immense potential for cardiac repair and regeneration. [1][2][3][4] Clinical use of adult stem cells is a reality today and many stem cell types, including bone marrow-derived mesenchymal stem cells (MSCs), 5 bone marrow cells, 7,8 cardiac-derived cardiac progenitor, 6 and cardio-sphere derived cells 9 have been tested. The beneficial effects of tested cell therapies on cardiac structure and function have been modest and most studies to date have not been adequately powered to document efficacy.…”
mentioning
confidence: 99%
“…Research from several laboratories, including ours, suggests that stem cells hold immense potential for cardiac repair and regeneration. [1][2][3][4] Clinical use of adult stem cells is a reality today and many stem cell types, including bone marrow-derived mesenchymal stem cells (MSCs), 5 bone marrow cells, 7,8 cardiac-derived cardiac progenitor, 6 and cardio-sphere derived cells 9 have been tested. The beneficial effects of tested cell therapies on cardiac structure and function have been modest and most studies to date have not been adequately powered to document efficacy.…”
mentioning
confidence: 99%
“…The precise mechanism of action has yet to be defined, but it may involve secretion of paracrine factors and stimulation of endogenous mechanisms of myocardial repair (3). As a therapeutic for adults, MSCs have recently emerged as a leading stem cell candidate based on a series of early phase clinical trials that have shown a favorable safety profile, feasibility as an allogeneic cell therapy product, and preliminary efficacy to improve contractility, quality of life, and reduce myocardial scar formation (11,12,20). Additionally, MSCs have shown the capacity to recruit and activate resident c-kit ϩ cardiac stem cells (CSCs), a myocardial compartment of undifferentiated progenitor cells, to areas of myocardial injury (13).…”
Section: We Demonstrate For the First Time That Intramyocardial Injecmentioning
confidence: 99%
“…The center of the scar on the endothelial border was noted, and scar thickness and wall thickness were measured at this point. Then, the same measurements were performed at half the distance between the center of the scar and the lateral edges of the scar, as previously described 6. Scar transmurality was calculated as the percentage of scar thickness over wall thickness.…”
Section: Methodsmentioning
confidence: 99%